RESPON PUPUK ORGANIK DARI BEBERAPA LIMBAH TERNAK BERBANDING UREA TERHADAP PERTUMBUHAN DAN PRODUKSI RUMPUT PAKCHONG (PENNISETUM PURPUREUM CV. THAILAND) SEBAGAI PAKAN TERNAK - Meriksa Sembiring; Bambang SAS; Risdawati Br Ginting (Jurnal Cakrawala Ilmiah, 2025)
Grass is the main feed for ruminant livestock which has an important role for survival and production. This study aims to meet livestock needs for green fodder, it is necessary to fertilize. increasing the productivity of pakchong grass (Pennisetum purpureum cv Thailand) by utilizing available resources from livestock manure as natural fertilizer. This study design used a non-factorial Randomized Block Design (RAK) consisting of 4 treatments and 6 replications, with K0 = Control (without manure), K1 = cow manure, K2 = goat manure and K3 = chicken manure. The use of manure uses 1 kg / m2 with fertilization a week before planting. Parameters throughout the study were plant height growth, number of tillers, leaf length, fresh weight and dry weight production. The data obtained were analyzed statistically, if the analysis showed a significant difference, then continued with testing using the DMRT test. The results of statistical analysis of each parameter of the influence of several uses of Manure (K) showed a significant difference (p <0.05) on each parameter observed, with the results of the use of chicken manure (K3) being the best in Pakchong grass planting followed by the use of goat manure (K2) and the use of cow manure (K1) was the lowest compared to the use of manure tested. The higher the concentration of EM4 used, the better it is for the parameters.